P76 Prospective investigation of pre-diagnostic urinary bisphenol a and phthalates in relation to endometrial cancer risk in the multiethnic cohort (MEC) study. (1st November 2019) - Sarink, D; Le Marchand, L; Cheng, I; Wu, AH; Franke, AA; Wilkens, LR; White, K; Yu, H; Merritt, MA
Abstract : Introduction/Background: In the Multiethnic Cohort (MEC) Study based in Hawaii and Los Angeles, the age-adjusted incidence of endometrial cancer (per 100, 000, ages 60–90) is highest in Native Hawaiians (112.0) vs. 68.9 in white women. Since endometrial cancer develops under conditions of high circulating estrogen levels, we hypothesized that exposure to estrogenically active BPA and phthalates will increase endometrial cancer risk and these associations may be most relevant for Native Hawaiian women who have high endometrial cancer incidence rates. Methodology: We initiated a nested case-control study to measure urinary BPA and phthalates from the MEC. We identified 146 postmenopausal endometrial cancer cases and controls matched 1:1 on race/ethnicity, area, birth year, fasting hours, urine type, date/time of collection and postmenopausal hormone use. Conditional logistic regression will be used to calculate odds ratios and 95% confidence intervals for the association between BPA or phthalate concentrations with endometrial cancer risk accounting for the matching criteria, creatinine concentration and endometrial cancer risk factors. Results: There were differences in endometrial cancer risk factors between the cases and controls; for example, cases were more likely to never use oral contraceptives (46% of cases vs. 39% of controls) and cases had a higher body mass index (32% of cases vs. 19% of controls with BMI ≥30 kg/m 2 ). There were no differences in the frequency of cases and controls who were parous or by education level. We are currently analyzing the associations with urinary BPA and phthalate metabolite concentrations and will present our findings at the meeting. Conclusion: To our knowledge this is the first study to examine the role of BPA and phthalates in relation to endometrial cancer risk using prospective samples and to explore whether risk associations differ across racial/ethnic groups. This work will highlight new avenues for further research that aim to correct observed endometrial cancer disparities. Disclosure: Nothing to disclose.